2009
DOI: 10.1007/s00012-010-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Free products of unital ℓ-groups and free products of generalized MV-algebras

Abstract: We show that the free product of any collection of non-trivial unitalgroups with fixed strong unit exists. Equivalently, the free product of any collection of non-trivial generalized MV-algebras exists. We then investigate free products in some of the varieties of these algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The main result in Dvurečenskij and Holland (2009c) says that the free product of any collection of non-trivial GMV-algebras exists in the variety of all GMV-algebras. If we restrict to particular families of GMV-algebras, it is possible to show that sometimes if the free product exists in a smaller family, so exists in a bigger one and both coincide (Dvurečenskij and Holland 2009c, Lem 4.2):…”
Section: Applications Of Cyclic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main result in Dvurečenskij and Holland (2009c) says that the free product of any collection of non-trivial GMV-algebras exists in the variety of all GMV-algebras. If we restrict to particular families of GMV-algebras, it is possible to show that sometimes if the free product exists in a smaller family, so exists in a bigger one and both coincide (Dvurečenskij and Holland 2009c, Lem 4.2):…”
Section: Applications Of Cyclic Elementsmentioning
confidence: 99%
“…The free product of MV-algebras was studied in Mundici (1988) and the free product of GMV-algebras was exhibit in Dvurečenskij and Holland (2009c): let V be a class of GMV-algebras and let fM t g t2T be a family of GMV-algebras in V: A V-free product (or simply a free product if V is known from the context) of this family is a GMV-algebra M 2 V; denoted by F V t2T M t ; together with a family of GMV-embeddings ff t : M t ! Mg t2T such that…”
Section: Applications Of Cyclic Elementsmentioning
confidence: 99%
“…an element u ∈ G + such that given g ∈ G, there is an integer n ≥ 1 such that g ≤ nu). Using this basic representation, a free product of GMV-algebras was studied in [5] and the free product of MV-algebras in [13]. In [5], it was shown that the free product of MV-algebras in the category of GMV-algebras can be non-commutative.…”
Section: Introductionmentioning
confidence: 98%
“…Using this basic representation, a free product of GMV-algebras was studied in [5] and the free product of MV-algebras in [13]. In [5], it was shown that the free product of MV-algebras in the category of GMV-algebras can be non-commutative. In what follows, using the bounded Boolean power, we show that the free product of an MV-algebra with a Boolean algebra 2 n taken in the category of GMValgebras is again an MV-algebra.…”
Section: Introductionmentioning
confidence: 98%
“…This provided a way to study varieties of pseudo MV-algebras by examining equational classes of "unital" lattice-ordered groups. Holland has been at the forefront of this research ever since and obtained major results in the last few years, with A. Dvurečenskij, M. R. Darnel and M. Droste [59,63,64,65,66,67,70,71,72].…”
mentioning
confidence: 99%